NAD+-Precursor Supplementation With L-Tryptophan, Nicotinic Acid, and Nicotinamide Does Not Affect Mitochondrial Function or Skeletal Muscle Function in Physically Compromised Older Adults. Issue 10 (30th June 2021) - Connell, N J; Grevendonk, L; Fealy, C E; Moonen-Kornips, E; Bruls, Y M H; Schrauwen-Hinderling, V B; de Vogel, J; Hageman, R; Geurts, J; Zapata-Perez, R; Houtkooper, R H; Havekes, B; et al.
ABSTRACT: Background: Boosting NAD + via supplementation with niacin equivalents has been proposed as a potential modality capable of promoting healthy aging and negating age-dependent declines of skeletal muscle mass and function. Objectives: We investigated the efficacy of NAD + -precursor supplementation (tryptophan, nicotinic acid, and nicotinamide) on skeletal muscle mitochondrial function in physically compromised older adults. Methods: A randomized, double-blind, controlled trial was conducted in 14 (female/male: 4/10) community-dwelling, older adults with impaired physical function [age, 72.9 ± 4.0 years; BMI, 25.2 ± 2.3 kg/m 2 ]. Participants were supplemented with 207.5 mg niacin equivalents/day [intervention (INT)] and a control product (CON) that did not contain niacin equivalents, each for 32 days. The primary outcomes tested were mitochondrial oxidative capacity and exercise efficiency, analyzed by means of paired Student's t -tests. Secondary outcomes, such as NAD + concentrations, were analyzed accordingly. Results: Following supplementation, skeletal muscle NAD + concentrations [7.5 ± 1.9 compared with 7.9 ± 1.6 AU, respectively] in INT compared with CON conditions were not significantly different compared to the control condition, whereas skeletal muscle methyl-nicotinamide levels were significantly higher under NAD + -precursor supplementation [INT, 0.098 ± 0.063 compared with CON, 0.025 ± 0.014; P = 0.001], suggesting an increased NAD + metabolism. Conversely, neither ADP-stimulated [INT, 82.1 ± 19.0 compared with CON, 84.0 ± 19.2; P = 0.716] nor maximally uncoupled mitochondrial respiration [INT, 103.4 ± 30.7 compared with CON, 108.7 ± 33.4; P = 0.495] improved under NAD + -precursor supplementation, nor did net exercise efficiency during the submaximal cycling test [INT, 20.2 ± 2.77 compared with CON, 20.8 ± 2.88; P = 0.342]. Conclusions: Our findings are consistent with previous findings on NAD + efficacy in humans, and we show in community-dwelling, older adults with impaired physical function that NAD + -precursor supplementation through L-tryptophan, nicotinic acid, and nicotinamide does not improve mitochondrial or skeletal muscle function. This study was registered at clinicaltrials.gov as NCT03310034.